Cranfield University centre of excellence in counter-terrorism - Forth, Shaun A.; Johnson, Stephen; Burrows, Stephanie J.; Sheldon, Robert (Cranfield University, 2018)
The formation of Cranfield University’s Counterterrorism Centre of Excellence was announced in late summer 2017. It has been established in conjunction with Pool Re, a mutual reinsurer which underwrites over £2 trillion of exposure to terrorism risk in the UK. The centre will provide thought leadership in catastrophic and unconventional terrorism loss assessment and mitigation so as to improve the UK’s economic resilience. We introduce the reinsurance industry for a technical audience to explain the rationale for the Counterterrorism Centre of Excellence. The centre’s aims and some results from preliminary simulations on explosive blast in a complex city centre performed in collaboration with reinsurance broker Guy Carpenter are presented. The prospects for physics-based simulation, for terrorist insurance loss estimation and for encouraging mitigation in reinsurance are outlined.
Keywords: Counterterrorism; CBRNE Centres of Excellence activities; Software and tools for safety and security; Economical issues related to CBRNE; Modelling and simulation